Par petits bouts - Lorena Poblete (Temporalités)
Analyzing four maids’ autobiographies written between 1975 and 2012, this article questions the way the temporal patterns specific to a given professional activity contribute to defining the structure of an autobiographical narrative. We analyze the new figures of speech introduced to tell the story of a life in which the core of the narrative is anchored in a particular social role and defined by a specific activity: cleaning other people’s houses. The body of texts chosen for the analysis allows us to put housemaids’ experiences in perspective. We will be using the autobiographies of Maria Arondo and Fatima Elayoubi, who migrated to France respectively from Spain and Morocco, as well as the narratives by Louise Rafkin and Isaure who, having earned a degree in literature, decided to live the life of a housemaid in order to tell about it. Despite their differences, these singular experiences have points in common and show up, each in its own way, the particular nature of that professional relationship.